2019
DOI: 10.1371/journal.pone.0225806
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7-adapter complex modulates interferon-α production in HIV-stimulated plasmacytoid dendritic cells

Abstract: Plasmacytoid dendritic cells (PDCs) and their production of interferon-alpha (IFN-α) are believed to play an important role in human immunodeficiency virus, type I (HIV-1) pathogenesis. PDCs produce IFN-α and other proinflammatory cytokines through stimulation of Toll-like receptor 7 (TLR7) and TLR9 present in endosomal compartments. TLR7 recognizes single-stranded viral RNA, while TLR9 recognizes unmethylated DNA. In this study, we examined the mechanisms that may underlie variations in IFN-α production in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This is in contrast to a study that reported detectable IFN-α levels after PBMCs of healthy subjects were stimulated with the same imiquimod concentration [ 59 ]. Diminished IFN-α production in plasmacytoid dendritic cells after stimulation with a TLR7 agonist has been reported previously in PLHIV [ 60 , 61 ], which might explain the undetectable IFN-α levels in both groups. The importance of IRF7 and type 1 interferon signaling pathways was recently also shown in studies exploring the role of RNA deadenylase complex, CNOT, in HIV infection.…”
Section: Discussionsupporting
confidence: 60%
“…This is in contrast to a study that reported detectable IFN-α levels after PBMCs of healthy subjects were stimulated with the same imiquimod concentration [ 59 ]. Diminished IFN-α production in plasmacytoid dendritic cells after stimulation with a TLR7 agonist has been reported previously in PLHIV [ 60 , 61 ], which might explain the undetectable IFN-α levels in both groups. The importance of IRF7 and type 1 interferon signaling pathways was recently also shown in studies exploring the role of RNA deadenylase complex, CNOT, in HIV infection.…”
Section: Discussionsupporting
confidence: 60%
“… 24 , 25 Primarily expressed in plasmacytoid DCs (pDCs), TLR7 identifies single‐stranded (ss) RNA found in viruses and acts as a small purine analog (imidazoquinoline); moreover, it identifies RNA from Streptococcus B bacteria in conventional DCs (cDCs), inducing type I IFN and proinflammatory cytokine production. 26 , 27 , 28 Human TLR8 is responsive to viral and bacterial RNA, and TLR8 is most similar phylogenetically to TLR7. TLR8 is expressed in a variety of tissues, is most highly expressed in monocytes, and is upregulated following bacterial or viral RNA stimulation, as well as inducing IFNs and inflammation‐related cytokine generation.…”
Section: Tlr and Ligand‐recognition Mechanismsmentioning
confidence: 99%
“…Endosomal TLRs might promote human immunodeficiency virus type 1 (HIV-1) replication and latency reversal via the stimulation of inflammatory responses [ 76 ]. TLR7 overexpression leads to the hypo-responsiveness of CD4+ T cells, and the production of IFN-α in HIV-1 replication [ 77 , 78 ]. TLR7 engagement in CD4+ T cells results in the dephosphorylation of transcription factor NFATc2 and then induces an anergic gene-expression program.…”
Section: Tlr7 Implication In a Variety Of Clinical Diseasesmentioning
confidence: 99%